2015
DOI: 10.1111/jfpp.12423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sumac (R hus coriaria  L.) and Barberry (B erberis vulgaris  L.) Water Extracts on Microbial Growth and Chemical Changes in Ground Sheep Meat

Abstract: The present study investigated the effect of sumac (SWE) and barberry water extracts (BWE) on microbial growth and chemical changes in ground sheep meat during refrigerated storage. The meat samples were explored for changes in total viable count (TVC), lactic acid bacteria (LAB), coliforms, yeasts and Listeria monocytogenes populations as well as thiobarbituric acid reactive substances (TBARS) value, metmyoglobin (metMb), pH value and sensory quality. The greatest antimicrobial effect of SWE was found on coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Sumac extract fortified wheat breads had extended shelf life and enhanced phenolic content along with unique textural and sensory properties (Wang & Zhu, 2018). Sumac inhibited microbial growth and lipid oxidation of ground sheep meat during refrigerated storage (Aliakbarlu & Mohammadi, 2015). Koobideh Kebab with sumac water extracts had extended shelf life and improved overall acceptability (Yadolahi‐Baghloei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sumac extract fortified wheat breads had extended shelf life and enhanced phenolic content along with unique textural and sensory properties (Wang & Zhu, 2018). Sumac inhibited microbial growth and lipid oxidation of ground sheep meat during refrigerated storage (Aliakbarlu & Mohammadi, 2015). Koobideh Kebab with sumac water extracts had extended shelf life and improved overall acceptability (Yadolahi‐Baghloei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sumac extract showed to be more effective than barberry extract in inhibiting microbial growth and in controlling chemical changes in the supplemented meat. The application of both extracts to ground sheep meat not only enhanced its sensorial properties but also prolonged its storage life [74]. Moreover, a study showed that Sumac was effective as a natural meat tenderizer [75].…”
Section: Application Of Sumac In Meatmentioning
confidence: 99%
“…Furthermore, L. nobilis is an aromatic plant widely exploited in the food sector, and therefore, its aroma could also be compatible with a meat product. Ibrahim et al (2011), Aliakbarlu and Mohammadi (2015), and Mashau et al (2021) studied the properties of other extracts not widely studied for food preservation when applied by mixing it with minced sheep meat. All the tested sources (extracts from Simmondsia chinensis, Jatropha curcas, Panax ginseng, Z. officinale, Rhus coriaria, Berberis vulgaris, and Moringa oleifera) reduced the initial load of microorganisms belonging to the microbial ecology of sheep meat, confirming the efficacy of the mixing technique.…”
Section: Application Of Plant Extracts On Sheep Meatmentioning
confidence: 99%
“…Ibrahim et al. (2011), Aliakbarlu and Mohammadi (2015), and Mashau et al. (2021) studied the properties of other extracts not widely studied for food preservation when applied by mixing it with minced sheep meat.…”
Section: Antimicrobial Properties Of Plant Extracts On Sheep Meatmentioning
confidence: 99%